A practical low-cost approach to build membrane electrode assemblies using decal transfer technique. (July 2018) - Yang, Sichang; Zhang, Xinyu; Wang, Bo; Huang, Hanzhe; Zhao, Zirui; Wang, Xinyuan; Yu, Kaili; Ahmadi, Goodarz
Abstract: Membrane electrode assembly (MEA) is the heart of a proton exchange membrane (PEM) fuel cell. In this paper, a practical and low-cost approach to build membrane electrode assemblies in lab using decal transfer technique is described and verified. The procedure is based on current literatures but using different materials for convenience and cost-saving. All devices and tools used are easy to find in normal labs and all materials used are affordable and easy to obtain from market. Two Membrane electrode assemblies are built and tested using a PEM fuel cell test and control system. Two MEAs showed voltages of about 0.82V and 0.70V respectively, measured with a digital multimeter, which are lower than that of the commercial MEA. It is found that the unscratched MEA with more catalyst has a lower voltage, but can generate higher current density and much water. Some water oozed through the bipolar plates which usually is not seen in a single cell test